Improvement of postharvest keeping quality of white pepper fruits (Capsicum annuum, L.) by hydrogen peroxide treatment under storage conditions - Bayoumi, Yousry A. (Acta Biologica Szegediensis, 2008)
Sweet pepper is one of the most important vegetable crops in the world, it has excellent nutritive value but it is susceptible to relatively fast quality changes after harvest time. The objective of the present research was to evaluate the effect of dipping pepper fruits in hydrogen peroxide solutions on postharvest keeping quality during storage time. Whole pepper fruits were soaked for 30 min in a solutions of hydrogen peroxide (0, 1, 5 and 15 mM) then, air dried and stored at room temperature (20ºC) for 2 weeks and in fridge (10ºC) for 4 weeks. Hydrogen peroxide treatments significantly reduced weight loss, rot rate index and nitrate content of fruits specially with 15 mM hydrogen peroxide as compared with control treatement (0 mM hydrogen peroxide). Moreover, hydrogen peroxide treatments significantly increased general appearance, ascorbic acid content and the activity of the antioxidant enzymes such as ascorbate peroxidase and dehydroascorbate reductase. For dry matter and TSS%, there are no significant differences among treatments. Therefore, the use of hydrogen peroxide in postharvest treatments have a good potential strategy to improve the postharvest quality, extend shelf life period and maintained some nutritional quality as well as inhibited decay development of white peppers which natural infected under storage conditions.